(untitled) (Global Journal of Medical Research, 2014)
Hematological and serum biochemical changes in cattle suffering from natural outbreak of Black quarter (BQ) in different areas of Punjab, Pakistan were studied. Blood samples from infected cattle were subjected to TLC, TEC, DLC, hemoglobin and PCV while serum samples for estimation of Cpk, ALT and AST (n=50). It was found that mean erythrocyte count decreased significantly (P < 0.05) while mean leukocyte count increased significantly (P < 0.05) in diseased animals. On the other hand mean Hb, platelets count and PCV in diseased animal did not differ significantly (P > 0.05) as compared to healthy animals.Average DLC values were found varying to great extent. It was found that mean neutrophils and lymphocytes (%) increased significantly (P < 0.05) while those of monocytes and basophils (%) increased non-significantly (P > 0.05) in diseased animals.